Characterization of Mathematical Reasoning Skills in Children with ADHD - Salvatierra Melgar, Angel (2019)
The objective of the present research was to characterize the mathematical reasoning skills in children with ADHD between 7 and 9 years old. The study begins with the conception of children with special needs and an anthropological research is carried out in perspectives of the actor on mathematical reasoning skills and interviews of their three teachers about their difficulties, alterations and disorders. The research method is an ethnographic fieldwork. The results show lack of mathematical skills specifically in numerical calculation; observing disorder, combination of simultaneous operation between addition and subtraction, attention deficit during the reading of a problem so they fail to systematize, identify data for algorithmic operations